Potential Clinical Use of CytoSorb® for Ticagrelor and Rivaroxaban Elimination Prior to Emergency Orthopedic Surgery in Trauma Patients - Gabriele Melegari; Fabio Gazzotti; Federica Arturi; Elisabetta Bertellini; Andrea Tognù; Domenico Pietro Santonastaso; Matteo Villani; Francesca Coppi; Fabrizio Fattorini; Fabio Catani; Alberto Barbieri (Life)
Background: Major orthopedic trauma in patients receiving anticoagulants such as ticagrelor or rivaroxaban poses a significant perioperative challenge, particularly in emergency contexts where bleeding risks are heightened and specific reversal agents may be unavailable. CytoSorb®, a hemoadsorption device, has demonstrated efficacy in cardiac surgery for drug removal. Its potential application in trauma surgery remains unexplored. Objective: This protocol describes a prospective clinical investigation assessing the feasibility and safety of CytoSorb® hemoadsorption for the preoperative removal of ticagrelor and rivaroxaban in trauma patients requiring urgent orthopedic surgery. Methods: The proposed intervention involves integrating CytoSorb® into a dedicated extracorporeal circuit under normothermic conditions (37 °C) with a blood flow of 150–200 mL/min for 300 min. Serial plasma samples will be collected at predefined intervals (0, 30, 60, 120, 240, 300 min) and drug concentrations. The primary outcome is the pharmacokinetic profile of drug clearance. Secondary endpoints include procedural safety, bleeding complications, and the feasibility of timely surgery. Expected Impact: The study aims to provide real-world data on the practical integration of CytoSorb® for anticoagulant removal in orthopedic trauma care, potentially facilitating earlier surgery and improving perioperative safety. Findings may inform future randomized trials and protocol standardization.